Diagnostic Value of the Neutrophil/Lymphocyte Ratio, Platelet/Lymphocyte Ratio, and Thrombocytosis in the Preoperative Investigation of Ovarian Masses - Yoshida, Adriana; Sarian, Luís Otavio; Marangoni, Marcos, Junior; Firmano, Isis Caroline; Derchain, Sophie Françoise (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To evaluate the diagnostic accuracy of cancer antigen 125 (CA125) and complete blood count (CBC) parameters, such as the neutrophil to lymphocyte ratio (NLR), the platelet to lymphocyte ratio (PLR), and thrombocytosis in patients with ovarian masses.Methods The present is a retrospective study conducted at a single tertiary hospital from January 2010 to November 2016. We included consecutive women referred due to suspicious adnexal masses. The CBC and CA125 were measured in the serum of 528 women with ovarian masses before surgery or biopsy. We evaluated the diagnostic performance of the NLR, PLR, platelets (PLTs), CA125, and the associations between them. We tested the clinical utility of the CBC parameters and CA125 in the discrimination of ovarian masses through decision curve analysis (DCA).Results The best balance between sensitivity and specificity was obtained by the associations of CA125 or PLTs ≥ 350/nL, with 70.14% and 71.66%, CA125 or PLTs ≥ 400/nL, with 67.30% and 81.79%, CA125 or PLR, with 76.3% and 64.87%, and CA125 or NLR, with 71.09% and 73.89% respectively. In the DCA, no isolated CBC parameter presented a higher clinical utility than CA125 alone.Conclusion We showed that no CBC parameter was superior to CA125 in the prediction of the malignancy of ovarian tumors in the preoperative scenario.
Keywords: adnexal masses; diagnosis; ovarian cancer; serum biomarkers; thrombocytosis